The torch of the testimony - Kennedy, John, 1925- (Bombay, India Gospel Literature Service, 1963)
Includes bibliographical references and indexes.
Contents : The foundation -- The church established -- Church order -- Signs of declension -- Change -- Heresies -- Reaction -- The church flattered -- Religion and the Gospel -- Torch bearers -- Gathering clouds -- The welcome rain of reform -- The churches continuing -- From the midst of tragedy -- Reformers of the Reformation -- The fruit of revival -- The remnant -- The witness spreads -- The torch of the testimony
Includes bibliographcal references and index.
Keywords: Church history